Gus Muhammad Arinal Haq's Strategy in Creating Hadith Memorizers at the Al-Aqobah 4 Islamic Boarding School in Jombang, East Java - Hidayah, Nurul; Lur Rochman, Kholil (CV. DYOQU PUBLISHING MANAGEMENT, 2025)
Background:The tradition of memorizing hadith is an essential part of maintaining the purity of Islamic teachings. However, in many Islamic boarding schools (pesantren), hadith memorization programs are not as popular as Quran memorization, requiring a systematic learning strategy to maintain the tradition's sustainability. Al-Aqobah 4 Islamic Boarding School in Jombang is one institution that consistently promotes hadith memorization programs through a structured approach. Aims:This study aims to analyze the strategies implemented by Islamic boarding school administrators in creating hadith memorizers, describe the strategies of students in memorizing and maintaining memorization, and identify supporting and inhibiting factors in the implementation of the hadith memorization program. Methods:The research used a descriptive qualitative approach with data collection techniques including observation, in-depth interviews, and documentation. Participants included Islamic boarding school administrators, accompanying religious teachers (ustadz/ustadzah), and students participating in the One Day One Hadith Five Verses program. Data analysis was conducted through data reduction, data presentation, and drawing conclusions. Result:The research results show that the tutors' strategies include daily memorization, understanding the meaning of hadith, structured repetition (takrir), talaqqi (recitation), and periodic evaluation. Students use various techniques such as understanding the context of hadith, rewriting, and conducting independent and group murojaah (recitation). Supporting factors include a conducive Islamic boarding school environment and intensive mentoring, while barriers include limited time, differences in memorization abilities, and a tendency to forget. Conclusion:The strategy implemented at Al-Aqobah 4 Islamic Boarding School has proven effective in developing hadith memorizers who not only master the text but also understand its meaning. This research emphasizes the importance of structured and sustainable learning management in hadith memorization programs and opens up opportunities for developing similar models at other Islamic educational institutions.